Foraminiferal marker taxa and their correlation potential for definition of the lower Serpukhovian boundary in the Urals - E. I. Kulagina; E. Yu. Bashlykova (Литосфера, 2020)
Research subject. The choice of the marker and the GSSP (Global Boundary Stratotype Section and Point) of the base of the Serpukhovian is currently one of the most urgent tasks of international stratigraphy. The first appearance datum (FAD) of the conodont Lochriea ziegleri in the lineage Lochriea nodosa – Lochriea ziegleri is proposed as a global marker for the lower boundary of the Serpukhovian Stage of the International Stratigraphic Scale. Foraminifers are widely used for the subdivision of the Carboniferous deposits and can serve as auxiliary markers. Materials and methods. In this paper, the stratigraphic distribution of the foraminiferal marker species Janischewskina delicatа, Neoarchaediscus postrugosus, Eolasiodiscus donbassicus, Monotaxinoides gracilis, Monotaxinoides subplanus is discussed. These species are used to define the lower boundary of the Serpukhovian in the Urals and in the East European Platform. Results. Data on the first descriptions of their holotypes are summarized. The distributions of these species in the sections of the western slope of the Urals (Kugarchi, Muradymovo, Ladeinaya), the eastern slope of the South Urals (“Verkhnyaya” Kardailovka, Bolshoi Kizil, Khudolaz), the Serpukhovian type sections of the Moscow Syneclise and the boreholes of the southeast of the East European Platform are compared. The published ranges of the marker species in the sections of Western Europe (Spain, France, and northern England), Morocco, Kazakhstan, and China, including the Naqing section are reviewed. Conclusion. In the shallow-water coral-brachiopod and bioherm facies of the Ural sections, two or three markers can be found simultaneously. In these sections, it is possible to unambiguously determine the lower boundary of the Serpukhovian. However, here, conodonts and ammonoids were not found. Deep-water cephalopod facies containing conodonts are not favorable for foraminifers. In sections where both conodonts and foraminifera are simultaneously encountered, the appearance of foraminiferal marker taxa and conodonts rarely coincide; however, the divergence is small. Regarding the marker taxa under study, their appearance has not been established in sediments older than those dated as the Serpukhovian.